The Benefits of Smoking Cessation - Nick R Anthonisen (Canadian Respiratory Journal)
In this issue of the Canadian Respiratory Journal, Demeter et al (pages 435-441) describe lung cancer outcomes in a recent Alberta cohort. Not much is new; outcomes are bad, not much better than they were when I was in medical school more than 40 years ago. This is a particularly sad state of affairs in view of the fact that lung cancer is a self-inflicted phenomenon related to smoking. Further, this has been known for 40 years, and only recently have lung cancer rates levelled off in men, though they have continued to increase in women.